Penerapan Restorative Justice Dalam Penologi Modern: Alternatif Pemidanaan Di Era Reformasi Hukum - Salsabila Ayu Pramita (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
The penal system in Indonesia is still dominated by a retributive approach, which focuses on punishing offenders. However, this approach faces various issues such as prison overcrowding, high recidivism rates, and ineffectiveness in prisoner rehabilitation and social reintegration. As an alternative, restorative justice has emerged in modern penology, emphasizing victim recovery, offender accountability, and community involvement in the resolution process. This study aims to analyze the implementation of restorative justice in Indonesia's penal system and compare it with the retributive approach. The research employs a normative juridical method by analyzing legislation, legal policies, and relevant literature. The findings reveal that restorative justice has been accommodated in various regulations in Indonesia, such as Law No. 11 of 2012 on the Juvenile Criminal Justice System, Police Regulation No. 8 of 2021, and the new Indonesian Criminal Code (KUHP). The implementation of this approach has proven to be more effective in reducing recidivism rates, alleviating prison overcrowding, and providing a more balanced sense of justice for victims and offenders. Therefore, optimizing the implementation of restorative justice policies is essential for making it a primary solution in Indonesia’s penal system.